Surgical Considerations and Challenges for Bilateral Continuous-Flow Durable Device Implantation. Issue 2 (March 2016) - Maltais, Simon; Womack, Sara; Davis, Mary E.; Danter, Matthew R.; Kushwaha, Sudhir S.; Stulak, John M.; Haglund, Nicholas
Abstract : The concept of biventricular support with durable centrifugal pumps is evolving, and the surgical strategy and best practice guidelines for implantation of right-sided devices are still unknown. We present optimal strategy for bilateral HeartWare continuous-flow ventricular assist device (HVAD) implantation in a series of four patients. Patients were implanted with the HVAD pumps simultaneously or sequentially. This report offers a perspective on surgical considerations such as right ventricular positioning, implications related to potential risks of obstruction from the tricuspid apparatus, the role if any of downsizing the outflow anastomosis, and considerations for speed adjustments. In this series, one patient died on support and three patients experienced pump thrombosis requiring device revision. All other patients survived until orthotopic heart transplantation, although one of these patients died from perioperative complications, 2 days posttransplantation. Surgical management of patients with medically refractory biventricular heart failure remains challenging and associated with a high incidence of pump thrombosis. Best practice guidelines from experts' consensus are still needed to address this challenging population.